Nestling development of Jackdaws "Corvus monedula" in agricultural landscape - Kamiński, Piotr; Jerzak, Leszek; Boehner, Joerg (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
A Jackdaw colony of over 200 nests, built in cavities of old willow trees along 3 km of a mall road running through meadows next to the river Narew in an agricultural landscape (15 km southwest of Białystok, NE Poland), was studied to determine nest locations and construction, onset of egg laying, incubation period, egg parameters, clutch size and hatching success, nestling growth and mortality, breeding success as well as predation.
Keywords: Jackdaw; Corvus monedula; breeding ecology; hatching success; breeding success; nestling mortality; predation